2021
DOI: 10.1021/acs.jpcc.1c05707
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Real-Space Distribution of Acetophenone Dimers on H-containing Pt(111)

Abstract: We present a mechanistic study on the formation and real-space distribution of acetophenone dimers on the H-containing Pt(111) surface. Their geometric configuration and the specific chemical nature are addressed by a combination of scanning tunneling microscopy (STM) and infrared reflected absorption spectroscopy (IRAS). The formation of different types of acetophenone dimers is reported here, which critically depends on the surface coverage of H species. When the surface coverage of H is close to a monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…To further explore the possible effects of strong lateral interactions between the coadsorbed ligands and the reaction intermediates, the reactivity of acrolein hydrogenation was investigated on the surface precovered with acetophenone, which was shown in our previous studies to be capable of undergoing strong intermolecular interactions. , Figures and show the kinetic data of propenol formation and the related IR spectra obtained under operational conditions, correspondingly. In these experiments, the surface was covered with different amounts of acetophenone, which can be tentatively divided into low (exposure: 0.12–0.30 L) and high (exposure: 0.78–1.10 L) AP coverages.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the possible effects of strong lateral interactions between the coadsorbed ligands and the reaction intermediates, the reactivity of acrolein hydrogenation was investigated on the surface precovered with acetophenone, which was shown in our previous studies to be capable of undergoing strong intermolecular interactions. , Figures and show the kinetic data of propenol formation and the related IR spectra obtained under operational conditions, correspondingly. In these experiments, the surface was covered with different amounts of acetophenone, which can be tentatively divided into low (exposure: 0.12–0.30 L) and high (exposure: 0.78–1.10 L) AP coverages.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we provided several examples of this kind of stabilization of the enol form of a carbonyl compound via formation of oligomer complexes, in which the enol species were stabilized by hydrogen bonding in oligomers. 9–16…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in our recent studies on acetophenone adsorption and hydrogenation over a Pt(111) model catalyst, we showed that a stable enol form of acetophenone can be formed. 9–11,13,15 However, it requires the formation of surface ketone–enol dimers or ketone–enol–enol trimers, in which the newly formed OH group of enol is stabilized by establishing a hydrogen bond with the O atom of a carbonyl group of neighboring ketone species. 9–11,13,15 The formation of dimer or trimer acetophenone species was found to be an activated process and the ketone–enol–enol trimers were shown to be stable on this surface even at relatively high (up to 350 K) temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Such specific sites can be created by functionalization of the metal surface with a 2D layer of organic ligand adsorbates, exhibiting strong lateral interactions with the reactants. By virtue of these reactant–ligand lateral interactions, the surface reaction can be directed toward the desired route, and the unwanted reactions become inhibited. The approach based on the lateral interactions between a reactant and a coadsorbed 2D ligand layer is currently being developed for numerous multipathway hydrogenation reactions, , such as selective hydrogenation of acetophenone, trans-stilbene and phenylacetylene hydrogenation over Pd and Rh nanoparticles functionalized with N-heterocyclic carbens, , selective hydrogenation 1-epoxy-3-butene on Pd nanoparticles precovered with n -alkanethiol, hydrogenation of acetophenone to phenylethanol over Pt nanoparticles functionalized with proline, and chemoselective hydrogenation of the CO bond in α,β-unsaturated aldehydes over Pt 3 Co nanocrystals precovered with an oleyamine array …”
Section: Introductionmentioning
confidence: 99%
“…They comprise the geometric and electronic effects altering the formation of the desired reaction intermediate, the dynamic changes in the chemical structure of the ligands under the reaction conditions as well as the details of mutual intermolecular interactions between ligand and reactant species . The decisive effects of intermolecular interactions between different types of surface species on their reactivity were shown also for other reactive systems including hydrogenation of carbonyl and ester compounds. ,, …”
Section: Introductionmentioning
confidence: 99%